Sociodemographic differences in dietary trends among Iranian adults: findings from the 2005-2016 Iran-WHO STEPS survey - Sara Ebrahimi; Rebecca M Leech; Sarah A McNaughton; Farshad Farzadfar; Erfan Ghasemi; Sahar Saeedi Moghaddam; Katherine M Livingstone (Cambridge University Press, 2023)
Abstract Objective: To examine trends in the intake of key food groups among Iranian adults between 2005 and 2016, overall, and according to sociodemographic characteristics. Design: Repeat cross-sectional data from the Iran-STEPwise approach to risk factor surveillance (Iran-WHO STEPS) 2005-2016 were analysed. Regression analyses were used to evaluate trends in the frequency of fruits, vegetables and fish intake and type of oil used over time. Interactions by sex, age and area of residence were examined. Setting: Iran. Participants: 225 221 Iranian adults. Results: The frequency of vegetables (β: −0·03; 95 % CI (−0·06, −0·00); P-trend = 0·030) and fish (β: −0·09; 95 % CI (−0·10, −0·08); P-trend < 0·001) intake and use of solid fat (OR: 0·70; 95 % CI (0·70, 0·72); P-trend < 0·001) declined, whilst the frequency of fruit intake (β-Coeff: 0·03, 95 % CI (0·01, 0·05); P-trend = 0·014) and liquid oil use (OR: 1·40; 95 % CI (1·3, 1·4); P-trend<0·001) rose. Rising trends in fruit intake were larger in mid-aged (40-60 years) and older (>60 years) adults (P-interaction < 0·001), whilst declines in vegetable (P-interaction < 0·001) and fish intake (P-interaction = 0·001) were larger in older adults. The declining use of solid fat was strongest in middle-aged and older adults (P-interaction = 0·035), while the increasing use of liquid oil was strongest in rural areas (P-interaction = 0·011). Conclusions: During the nutrition transition, liquid oil use and the frequency of fruit intake rose, while the frequency of vegetables and fish intake declined. Nonetheless, the fatty acid composition and cooking methods are important considerations. The changes observed are concerning from a public health perspective and demonstrate the need for interventions and possible targets for tailored strategies.